Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on the Republic of Lithuania discusses structure of the financial sector, banking system vulnerabilities, and challenges. Rapid credit growth has been channeled into consumer and real estate lending, and is increasingly financed by foreign borrowing. The financial soundness indicators (FSIs) suggest a sound banking system, but may be lagging measure for financial system health. The current stress tests do not include a scenario with an economy-wide recession that could describe broader systemic risks to the banking system.